1998
DOI: 10.1161/01.hyp.31.1.315
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Hemodynamics and Regional Blood Flow During Chronic Nitric Oxide Synthesis Inhibition in Pregnant Rats

Abstract: Abstract-Pregnancy-induced hypertension m women 1s associated with severe vasoconstrlctlon and reductions m organ blood flow and cardiac output Recent studies have mdlcated that mtnc oxide (NO) synthesis mhlbltlon durmg mid to late gestation m pregnant rats results m severe hypertension and protemuna The purpose of this study was to determme the systemic hemodynamlc and regonal blood flow alterations associated with chronic NO synthesis mhlbltlon m the pregnant rat The study was conducted m four groups of rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
3
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 27 publications
4
45
3
1
Order By: Relevance
“…The growth inhibition of L-NAME in the renal sub-capsular assay may be partially due to a decrease in renal blood flow. Kassab et al (1998) previously demonstrated a decreased renal blood flow after administration of NO inhibitors, which is confirmed in our study by elevated creatinine and urea levels. Therefore, conclusions concerning anti-tumour effect of NO inhibitors from the data obtained in the renal sub-capsular assay cannot be drawn, but these data strongly suggest a growth inhibitory effect on the tumour by NO inhibitors.…”
Section: Discussionsupporting
confidence: 91%
“…The growth inhibition of L-NAME in the renal sub-capsular assay may be partially due to a decrease in renal blood flow. Kassab et al (1998) previously demonstrated a decreased renal blood flow after administration of NO inhibitors, which is confirmed in our study by elevated creatinine and urea levels. Therefore, conclusions concerning anti-tumour effect of NO inhibitors from the data obtained in the renal sub-capsular assay cannot be drawn, but these data strongly suggest a growth inhibitory effect on the tumour by NO inhibitors.…”
Section: Discussionsupporting
confidence: 91%
“…[32][33][34] Numerous studies have shown that inhibition of NO production by inhibitors specific for nitric oxide synthase (NOS) during pregnancy in the rat results in marked elevations in arterial pressure, proteinuria, intrauterine growth restriction, and attenuation of the mid-gestational increases in renal vasodilation, all features characteristic of women with preeclampsia. 14,17,18 In addition, reversal of NO-blockade mediated effects in the pregnant rat occur in treatment with L-arginine, the precursor for NO. 16,19 Thus, impairment of the NO pathway may play a role in mediating the pathophysiology of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…All dams in both groups littered spontaneously between day 22 and day 23 of gestation; mean duration of pregnancy was similar in the two groups [ 8 -18) in the L-NAME group and 15 Ϯ 1.5 (range, [12][13][14][15][16][17] in the control group; p Ͼ 0.05]. The day of birth was defined as postnatal day 0.…”
Section: Methodsmentioning
confidence: 99%